Influences of split application and nitrification inhibitor on nitrogen losses, grain yield, and net income for summer maize production - Ren, Baizhao; Ma, Zhentao; Zhao, Bin; Liu, Peng; Zhang, Jiwang (Frontiers in Plant Science, 2022)
The application of nitrogen (N) fertilizer combined with nitrification inhibitor is considered to be one of the effective strategies to improve N efficiency and reduce N loss. While the chemical and physical properties of nitrapyrin (CP) in fertilizers have been evaluated to increase N efficiency, a lack of comprehensive evaluation of the effects of adding CP on summer maize yield, environmental benefits and economic income under different fertilization methods. In this study, two fertilization methods were used: split-N application and one-time basal N fertilizer before sowing. The comprehensive effects of N fertilizer with CP on N loss (NH3 volatilization, NO3- leaching, and N2O emissions), N efficiency, yield and profit under two N application methods were explored. Results showed that under the two N application methods, N fertilizer with CP treatment increased the N efficiency and yield (+3.4%~+5.7%), significantly reduced the soil NO3--N content and N2O emissions, while increased NH3 volatilization. Especially, the increase amplitude of NH3 was much less than the decrease amplitude of N2O induced by adding CP. Although split-N application could achieve higher yield and N efficiency, N2O emissions and NH3 volatilization also increased. However, the T1+N (one-time basal N fertilizer before sowing mixed with CP) achieved the same yield level as T2 treatment (split-N application). Taking agronomic, economic and environmental benefits into consideration, one-time basal N fertilizer before sowing mixed with CP could ensure the target yield, increase economic benefits, maintain soil N content, and reduce N losses. Therefore, optimizing N management is essential to the sustainable development of agriculture.